Can engaging L2 teachers as material designers contribute to their professional development? findings from Colombia. (July 2020) - Banegas, Darío Luis; Corrales, Kathleen; Poole, Paige
Abstract: There is a lack of research around the professional development of English (L2) teachers in Colombia. As in other Latin American countries, higher education institutions have started offering general English as a foreign language (EFL) courses as well as content courses taught in English. In both types of course, EFL teachers are expected to integrate content and English language learning with the aim of providing learners with meaningful and authentic learning opportunities. However, such teachers often face the challenge of not having appropriate materials to deliver such courses. The aim of this case study, which employed mixed methods, is to describe the extent to which university EFL teachers from a Colombian university developed professionally as they engaged in developing materials for content and language integrated learning (CLIL) courses. The study consisted of two parts: (1) a CLIL workshop attended by 16 participants, followed by (2) interviews with four of those participants. Drawing on data from a survey, group discussions, and individual interviews, the findings show that engaging the university EFL teachers as materials developers boosted their professional knowledge (linguistic, content, and pedagogical knowledge), motivation, identity, and agency as CLIL teachers and material designers. Highlights: EFL teachers working within a CLIL approach can experience professional development through materials development. Through developing CLIL materials, the teachers enhanced motivation, agency, and identity. Engaging teachers in materials development lead to increased linguistic, pedagogical and content knowledge.